2003
DOI: 10.1258/135763303769211283
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of telemedicine and new media: a survey of Austrian medical students

Abstract: Telemedicine and new media (e.g. the Internet, tele-teaching and tele-learning) are increasingly being used in medicine. We surveyed the awareness and acceptance of these developments on the part of medical students (n =750) at the University of Innsbruck. A 16-item questionnaire was handed out in randomly chosen medical classes and collected immediately after completion, which resulted in a response rate of 99.9%. Nearly all of the students used the Internet regularly (68%) or at least sometimes (30%). Teleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…More than 4/5th of the respondents agreed or strongly agreed that telemedicine can improve the healthcare system, and that telemedicine services should be maintained with proper channels in tertiary care hospitals. These results are consistent with the findings of another cross sectional study which demonstrated that 79% of medical students in Austria highly rated the future importance of telemedicine ( 16 ). Similarly, a study by Yaghobian et al showed that 60% of medical students in France recognized the relevance of telemedicine in improving patient care while 82.5% of them also believed that telemedicine may result in improved access to healthcare ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More than 4/5th of the respondents agreed or strongly agreed that telemedicine can improve the healthcare system, and that telemedicine services should be maintained with proper channels in tertiary care hospitals. These results are consistent with the findings of another cross sectional study which demonstrated that 79% of medical students in Austria highly rated the future importance of telemedicine ( 16 ). Similarly, a study by Yaghobian et al showed that 60% of medical students in France recognized the relevance of telemedicine in improving patient care while 82.5% of them also believed that telemedicine may result in improved access to healthcare ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another major reason for this unsatisfactory level of knowledge is the absence of telemedicine training courses in the curricula of medical universities, as merely 9.5% of the respondents of our study cited their medical university as the source of knowledge for telemedicine. This is in conjunction with another study in which university lectures were quoted by only 21% of the students as the primary source of information about telemedicine ( 16 ). Previous literature suggests that the introduction of telemedicine education and training modules at a German medical university helped students improve their knowledge, skills and attitudes toward telemedicine ( 17 ).…”
Section: Discussionsupporting
confidence: 74%
“…Many of these studies (seven cases) reported positive and promising perspectives on telemedicine. 14 , 17 , 18 , 19 , 20 , 22 , 23 However, in one study, participants revealed moderate attitudes toward online health information and online health experience sharing ( p < 0.05). 15 …”
Section: Resultsmentioning
confidence: 90%
“… 19 The sample size of the studies ranged from 60 (Ehteshami et al 16 ) to 3312 (Yaghobian et al 22 ) participants, or 6172 participants on the whole. Four studies used in‐person questionnaires, 14 , 16 , 17 , 20 while the other six distributed online questionnaires among participants. 15 , 18 , 19 , 21 , 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…Telemedicine is being used increasingly in many parts of the world, with Canada and Scandinavia in particular leading the way. [2][3][4][5] In Australia, the demand for psychiatry services in remote areas was the initial driving force. Noting the paucity of literature on teaching this subject, we developed a new lesson to introduce the students to this specialised form of consultation.…”
Section: Introductionmentioning
confidence: 99%